THE EFFECT OF REALITY THERAPY ON THE SEROTONIN LEVEL AND DEPRESSION SCORE IN CERVICAL CANCER PATIENTS - Soetrisno Soetrisno; Supriyadi Hari Respati; Sultoni Emillya Anggraeni; Sri Sulistyowati (Nusantara Medical Science Journal, 2017)
ABSTRACT Introduction: Cervical cancer is cancer occurring in the cervix uteri, which is mostly caused by an  infection by human papillomavirus (HPV). Women  diagnosed with advanced cervical cancer suffer emotional stress that can  lead to depression. This condition causes decreasing quality of life, decreasing level of serotonin, and an increase in depression score. Giving reality therapy to patients is expected to have  positive effects. Methods: The  research was con- ducted through  an experiment with pre-test and post-test design. The research samples were15 subjects taken through consecutive sampling from the Polyclinic of Obstetrics and Gynecol- ogy of Dr. Moewardi Hospital Surakarta starting in March 2015. The analysis of serotonin level was conducted in Prodia Laboratory. The experimental data  was analyzed using a t-test (α =0.05).  Results: The average level of serotonin of the research subjects after receiving reality therapy was higher (223.59 + 41.20)  compared to that  before the  therapy (82.77  + 27.02). From  the t-test analysis with p = 0.00,  it was found that  the  average depression score after receiving  reality therapy is lower (11:40  + 4.80)  compared that  before the  therapy (17:33  +5:52).  Conclusion: There  was a significant increase in the  serotonin level and  a significant decrease in the  depression score as the  effect  of reality  therapy given  to patients with ad- vanced cervical cancer. Keywords: Serotonin, depression score, reality therapy, advanced cervical cancer